1990
DOI: 10.1159/000195878
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Bronchoalveolar Tumor

Abstract: We report the case of a young woman presenting productive cough and arthralgia in the left ankle. Chest radiography revealed multiple bilateral pulmonary nodules and abdominal echography and computerized axial tomography demonstrated various hepatic nodules. Definitive diagnosis of an intravascular bronchoalveolar tumor was reached by an open pulmonary biopsy. Liver involvement was confirmed by laparoscopy and biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Laboratory data revealed that alkaline phosphatase was increased in three patients and that two of them proved to have liver metastases. Gammaglobulinaemia was noticed only in two patients 13,14 …”
Section: Review Of the Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Laboratory data revealed that alkaline phosphatase was increased in three patients and that two of them proved to have liver metastases. Gammaglobulinaemia was noticed only in two patients 13,14 …”
Section: Review Of the Literaturementioning
confidence: 98%
“…A Medline search was performed to collect data on previously published cases of PEH and 13 authors in Japan, Belgium and USA were contacted to obtain full patient data. In this review, we studied the data of 93 patients, 4–64 including our patient by Cox regression analysis using forward stepwise method (SPSS version 9, SPSS, Chicago, IL, USA) to identify the risk factors and the independent predictors of survival in patients with PEH.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation